DIGITAL MARKETING TRAINING TO INCREASE INDUSTRIAL SALES IN MARINDAL VILLAGE - Sugito; Dina Hastalona; Anto Tulim; Rayu Sri Wahyuni; Taufik Azmi Harahap; Purnaa Sari Tarigan (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This Community Service (PKM) activity aims to increase the capacity of small and medium enterprises (SMEs) in Marindal Village to utilize digital marketing as a marketing strategy to expand their market and increase sales. The methods used included situational analysis, training, mentoring, and evaluation using pre- and post-test instruments. The results of the activity showed a significant increase in participants' understanding of digital marketing concepts (28% to 90%), business account creation skills (15% to 80%), and digital content creation skills (10% to 75%). In addition, there was a shift in marketing patterns from conventional to digital-based systems, which resulted in increased product visibility and business confidence in managing their businesses. However, challenges such as limited internet infrastructure, low digital literacy among some participants, and a lack of consistent promotions remain obstacles that need to be overcome. This PKM activity concluded that implementing digital marketing is an effective strategy in increasing the competitiveness of SMEs, with the note that ongoing mentoring and digital infrastructure support are needed.